2019
DOI: 10.1111/cge.13664
|View full text |Cite
|
Sign up to set email alerts
|

Who should access germline genome sequencing? A mixed methods study of patient views

Abstract: Implementation of any new medical test, including germline genome sequencing (GS) to inform cancer risk, should take place only when a test is effective, ethically justifiable and acceptable to a population. Little empirical evidence exists on patient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Participants in our study were interested in receiving personal risk information for conditions that they perceived to be relatively common, particularly cancer, although they were recruited via a cancer research database. Another Australian study conducted among cancer patients and their relatives found high enthusiasm for offering genome sequencing to the general population, prioritising those with a family history of cancer [31]. In a population sample not selected for their personal or family history of cancer, a Canadian study found stronger support for population genomic sequencing for colorectal cancer risk than type 1 diabetes, when conducted alongside existing screening strategies [14].…”
Section: Discussionmentioning
confidence: 99%
“…Participants in our study were interested in receiving personal risk information for conditions that they perceived to be relatively common, particularly cancer, although they were recruited via a cancer research database. Another Australian study conducted among cancer patients and their relatives found high enthusiasm for offering genome sequencing to the general population, prioritising those with a family history of cancer [31]. In a population sample not selected for their personal or family history of cancer, a Canadian study found stronger support for population genomic sequencing for colorectal cancer risk than type 1 diabetes, when conducted alongside existing screening strategies [14].…”
Section: Discussionmentioning
confidence: 99%
“…This reduced turnaround time has meant genomic sequencing can be applied to time-critical settings, such as for patients in neonatal and paediatric intensive care units (NICU and PICU). In the NICU, rGT achieves a diagnostic yield between 30% and 52% [ 8 , 9 , 10 ] and is a cost-effective and practical option for testing [ 2 , 5 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…GS is still expensive in the community (~USD4000 on commencement of this study), and it is known that many patients who are interested in testing do not pursue it due to cost [14]. Adult GS is not publicly funded in Australia.…”
Section: Introductionmentioning
confidence: 99%